(Feminist) STS and Autobiography: Early Inspirations, Current Concerns. (2nd January 2021) - Clarke, Adele E.
ABSTRACT: This contribution first describes early, largely progressive influences on STS and myself, sketching diverse groups concerned with sciences, technologies and especially medicines. I then turn to my own early activist concerns and their later scholarly and other manifestations, situating my feminist women's health activism and development as an early transdisciplinary STS scholar increasingly nourished transnationally. Last, I reflect on where I now stand, with feminist and other STS colleagues, and what we face at this point in the twenty-first century – some anguished yet hopeful intersections of history and autobiography.